INTENSITAS PENGGUNAAN CHATGPT TERHADAP KREATIVITAS DAN PRODUKTIVITAS MAHASISWA:TINJAUAN LITERATUR SISTEMATIS - Sri Muliani Sulastri; Setiawan Assegaff; Sharipuddin (Jurnal Teknologi Informasi Mura (JTI), 2026)
The use of ChatGPT in students' academic activities has grown rapidly, yet research findings on its influence on creativity and productivity remain scattered and have not been systematically synthesized. This study aims to map the theories, variables, methods, and findings of prior studies on ChatGPT usage intensity and its impact on students' creativity and productivity. A Systematic Literature Review (SLR) was conducted following the Kitchenham and Charters guidelines, searching the Scopus, Science Direct, and Google Scholar databases for the 2019-2025 period using the keywords ChatGPT, usage intensity, creativity, and student productivity. After a selection process based on inclusion and exclusion criteria, relevant articles were analyzed and synthesized. The review shows that Technology Acceptance Model 2 (TAM 2) and End User Computing Satisfaction (EUCS) are the most frequently used theoretical frameworks for explaining ChatGPT usage intensity, with Structural Equation Modeling-Partial Least Squares (SEM-PLS) as the dominant analytical method. This review also identifies a research gap: few studies have simultaneously integrated TAM 2 and EUCS to explain the relationship between usage intensity, creativity, and productivity among students. These findings provide a conceptual basis for developing a subsequent empirical research model.